1994
DOI: 10.1103/physrevlett.73.2994
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of Intense Laser Beams Due to Filamentation

Abstract: Channeling and filamentation of a laser beam is investigated experimentally and via computer simulations.A two-dimensiotial, fully nonlinear, fluid code has been developed and used to simulate the pmpagation of a 1aser pulse through an underdense plasma when v /v, -1. Comparison to interferometrically measured density depressions shows good agreement. The limited axial extent of the density perturbation seen in experiment is linked by the simulation to filamentation and divergence of the laser beam. A characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 21 publications
5
36
0
Order By: Relevance
“…At higher irradiation intensities (Ͼ10 14 W/cm 2 ) the radiation pressure can be sufficiently large with respect to the plasma pressure to significantly alter the electron density profile by excluding the plasma from regions of otherwise high density. [31][32][33] In recent soft x-ray laser interferometry studies of seemingly typical laserplasmas, where the ponderomotive force and other effects associated with high irradiation intensities are negligible, we observed 11 plasma density distributions that differ significantly from the expected classical conical expansion. That investigation was conducted using the DGI soft x-ray laser setup described above to map the dynamics of a line-focus plasma created by irradiation of a polished Cu slab target with ϭ1.06 m Nd:YAG laser pulses of ϳ13 ns FWHM duration.…”
Section: B Study Of Two-dimensional Effects In a Spot-focus Laser-crmentioning
confidence: 66%
“…At higher irradiation intensities (Ͼ10 14 W/cm 2 ) the radiation pressure can be sufficiently large with respect to the plasma pressure to significantly alter the electron density profile by excluding the plasma from regions of otherwise high density. [31][32][33] In recent soft x-ray laser interferometry studies of seemingly typical laserplasmas, where the ponderomotive force and other effects associated with high irradiation intensities are negligible, we observed 11 plasma density distributions that differ significantly from the expected classical conical expansion. That investigation was conducted using the DGI soft x-ray laser setup described above to map the dynamics of a line-focus plasma created by irradiation of a polished Cu slab target with ϭ1.06 m Nd:YAG laser pulses of ϳ13 ns FWHM duration.…”
Section: B Study Of Two-dimensional Effects In a Spot-focus Laser-crmentioning
confidence: 66%
“…Since the instability has a preferred wavelength, it could be detected by looking at the angular distribution of the transmitted light; the angle of deflection is given by where [5,6] and vo is the electron oscillatory velocity in the laser field, ve is the electron thermal velocity, O p e is the electron plasma frequency, and 00 (ko) is the frequency (wavenumber) of the incident laser.…”
Section: Ps Resultsmentioning
confidence: 99%
“…Simulations with a modified version of the F3D code [3] that includes nonlinear motion of the ions [4] suggested that the channels were being terminated by the onset of the filamentation instability [5]. Since the instability has a preferred wavelength, it could be detected by looking at the angular distribution of the transmitted light; the angle of deflection is given by where [5,6] and vo is the electron oscillatory velocity in the laser field, ve is the electron thermal velocity, O p e is the electron plasma frequency, and 00 (ko) is the frequency (wavenumber) of the incident laser.…”
Section: Ps Resultsmentioning
confidence: 99%
“…A nonlinear medium is susceptible to filamentation instability, which is characterized by growing electron density and irradiance fluctuations, transverse to the direction of propagation of the beam. There are two complementary approaches to the study of the filamentation instability in a plasma, as discussed by In the first usual approach (Askaryan,1962;Talanov, 1966;Hora, 1967;Palmer, 1971;Kaw et al, 1973;Max et al, 1974;Drake et al, 1974;Mannheimer and Ott, 1974;Perkins and Valeo, 1974;Yu et al, 1974;Chen, 1974;Sodha et al, 1976a;Sodha et al, 1976b;Bingham and Lashmore, 1976;Sodha and Tripathi, 1977;Gurevich, 1978;Perkins and Goldman, 1981;Kruer et al, 1985;Epperlein, 1990;Berger et al, 1993;Ghanshyam and Tripathi, 1993;Wilks et al, 1994;Kaiser et al, 1994;Vidal and Johnston, 1996;Lal et al, 1997;Guzdar et al, 1998;Bendib et al, 2006;Keskinen and Basu, 2003;Gondarenko et al, 2005), one considers an  refer to the components of the wave number k of the instability parallel and perpendicular to the direction of propagation viz., z axis. The instability grows or not, as the beam propagates, depending on whether k || is imaginary or real.…”
Section: Introductionmentioning
confidence: 99%